Returns to Low-Skilled International Migration : Evidence from the Bangladesh-Malaysia Migration Lottery Program - Mobarak, Mushfiq; Sharif, Iffath; Shrestha, Maheshwor (World Bank, Washington, DC, 2020)
Many economists believe that the returns to migration are high. However, credible experimental estimates of the benefits of migration are rare, particularly for low-skilled international migrants and their families. This paper studies a natural experiment in Bangladesh, where low-skilled male migrant workers to Malaysia were selected via a large-scale lottery program. This study tracked the households of lottery applicants and surveyed 3,512 lottery winners and losers. Five years after the lottery, 76 percent of the winners had migrated internationally compared with only 19 percent of the lottery losers. Using the lottery outcome as an instrument, the paper finds that the government intermediated migration increased the incomes of migrants by over 200 percent and their household per capita consumption by 22 percent. Furthermore, low-skilled international migration leads to large improvements in a wide array of household socioeconomic outcomes, including female involvement in key household decisions. Such large gains arise, at least in part, due to lower costs of government intermediation.